Fabrication of Detonation Nanodiamonds Containing Silicon‐Vacancy Color Centers by High Temperature Annealing. Issue 19 (5th October 2021) - Shimazaki, Konosuke; Kawaguchi, Hiroki; Takashima, Hideaki; Segawa, Takuya Fabian; So, Frederick T.-K.; Terada, Daiki; Onoda, Shinobu; Ohshima, Takeshi; Shirakawa, Masahiro; Takeuchi, Shigeki
Abstract : Detonation Nanodiamonds Detonation nanodiamonds (DNDs) have attracted attention as single photon emitters with potential in many research fields. In article number 2100144 by Takuya Fabian Segawa, Shigeki Takeuchi, and co‐workers, silicon‐vacancy (SiV) color centers are created in DNDs with sizes below 10 nm by an annealing treatment up to 1100 °C in vacuum. A sharp emission line is observed at 737 nm, which agrees with the emission line of SiV centers.